Evaluating the association of frailty with communication about aging‐related concerns between older patients with advanced cancer and their oncologists. Issue 5 (11th November 2021) - Gilmore, Nikesha; Xu, Huiwen; Kehoe, Lee; Kleckner, Amber S.; Moorthi, Kiran; Lei, Lianlian; Mohamed, Mostafa R. S.; Loh, Kah Poh; Culakova, Eva; Flannery, Marie; Ramsdale, Erika; Duberstein, Paul R.; et al.
Abstract : Background: A geriatric assessment (GA) intervention improves communication about aging‐related concerns, but its effect on communication in patients with various levels of frailty is unknown. Methods: This was a secondary analysis of a nationwide trial of patients aged ≥70 years with incurable cancer and impairment on 1 or more GA domains (ClinicalTrials.gov Identifier NCT02107443; principal investigator Supriya G. Mohile). Practice sites were randomized to either the GA‐intervention or usual care. Frailty was assessed with a deficit accumulation index (range, 0‐1), and patients were stratified as robust (0 to <0.2), prefrail (0.2 to <0.35), or frail (≥0.35). The clinic visit after the GA‐intervention was audio‐recorded, transcribed, and coded to evaluate the number and quality of conversations about aging‐related concerns. Linear mixed models examined differences in the number and quality of conversations within and between arms. All P values were 2‐sided. Results: Patients (n = 541) were classified as robust (27%), prefrail (42%), or frail (31%). In the usual care arm, frail patients (vs robust ones) engaged in more aging‐related conversations (adjusted mean difference, 1.73; 95% confidence interval [CI], 0.59‐2.87), conversations of higher quality (difference, 1.12; 95% CI, 0.24‐2.0), and more discussions about evidence‐based recommendations (difference, 0.71; 95% CI, 0.04‐1.38; all P values ≤ .01). Similarly, in the GA intervention arm, frail patients (vs robust ones) engaged in more aging‐related conversations (difference, 2.49; 95% CI, 1.51‐3.47), conversations of higher quality (difference, 1.31; 95% CI, 0.56‐2.06), and more discussions about evidence‐based recommendations (difference, 0.87; 95% CI, 0.32‐1.42; all P values ≤ .01). Furthermore, the GA‐intervention significantly improved the number and quality of conversations in all patients: robust, prefrail, and frail (all P values ≤ .01). Conclusions: Patients with higher degrees of frailty and those exposed to the GA‐intervention had more and higher quality conversations about aging‐related concerns with oncologists. Lay Summary: A geriatric assessment (GA) intervention improves communication about aging‐related concerns, but its effect on communication in patients with various levels of frailty is unknown. This study conducted a secondary analysis of a nationwide trial of patients aged ≥70 years with incurable cancer and 1 or more GA domain impairments. Patients were stratified as robust, prefrail, or frail. The number and quality of conversations about aging‐related concerns that occurred during the clinic visit after the GA‐intervention were determined. Patients with higher degrees of frailty and those in the GA intervention arm had more and higher quality conversations about aging‐related concerns with oncologists. Abstract : A geriatric assessment (GA) intervention improves communication about aging‐related concerns, but its effect on communication in patients with various levels of frailty is unknown. This study shows that patients with higher degrees of frailty and those in a GA intervention arm have more and higher quality conversations about aging‐related concerns with oncologists.